Merchant electricity transmission expansion: A European case study - Tarjei Kristiansen; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We apply a merchant transmission model to the trilateral market coupling (TLC) arrangement among the Netherlands, Belgium and France as a generic example, and note that it can be applied to any general market splitting or coupling of Europe's different national power markets. In this merchant framework; the system operator allocates financial transmission rights (FTRs) to investors in transmission expansion based upon their preferences, and revenue adequacy. The independent system operator (ISO) preserves some proxy FTRs to deal with potential negative externalities due to an expansion project. This scheme proves to be capable in providing incentives for investment in transmission expansion projects within TLC areas.
Keywords: L51; L91; L94; Q40; 330; Transmission expansion; trilateral market coupling; Europe; financial transmission rights; congestion management